Identification of facilitating factors for effective implementation of Islamic work ethics - Melati, Putifatma Hanum; Mohd Mahudin, Nor Diana (2014)
Studies have shown that the implementation of workplace ethics is a challenging task, but in the face of organisational change, a necessary effort. Therefore, the use of an adequate strategy to implement workplace ethic policies in general and Islamic work ethics (IWE) in particular, has been recommended. Implementing the Islamic work ethics in an organisation may sound straightforward in theory, but in practice, few issues may still arise. The proposed study aims to establish what is known regarding issues that facilitates the implementation of Islamic work ethics in organisations and to make recommendation for the implementation of this work ethics in organisations. To fulfil these aims, some possible facilitating factors for successful implementation will be explored via a questionnaire, which will be distributed to employees from various Islamic banking organisations. Quantitative data obtained will be analysed using descriptive statistics, correlations, and simple linear regression analysis. Findings will result in a series of recommendation strategies for enhancing the implementation of work ethics in workplace. We believe that the proposed study offers two significant contributions in the topic area. First, organisations could develop useful strategy management to encourage employees to apply the Islamic work ethics based on the factors identified in this study; and, second, positive work outcomes would be increased with the effective adoption and implementation of the Islamic work ethics.